PENGGUNAAN BAHASA DAERAH SEBAGAI BAHASA PENGANTAR DI KELAS RENDAH SEKOLAH DASAR DI KOTA PALANGKA RAYA - Muston Sitohang (Balai Bahasa Kalimantan Tengah, 2017)
The use of Bahasa Indonesia as the language of instruction in the education process is a must. However, sometimes in some cases, the use of local language is needed by teachers in order to encourage better communication to students. This is a descriptive research. The purpose of the paper is to know the use of local language as the language of instruction at the primary school level. The findings of this study indicate that teachers in the early grades, first to third grade, at the primary school level still use local language as an introduction other than Indonesian. In accordance with most respondents, local language is very helpful for them in providing and building deeper understanding to students